Synthesis And Characterization Of Magnetized Fe3o4-zro2 Catalysts For Methyl Ester Production From Waste Cooking Oil - Muhammad Fareez Naufal Fadilah; Balqis Adlina Omar; Farah Wahida Harun; Salina Mat Radzi; Nurul Jannah Abd Rahman (Malaysian Analytical Sciences Society, 2025)
Indexed by Scopus (Tier 2)